A Reflective Teaching Journey Through The Kampus Mengajar Batch 7 Program - Aisa Fitri; Musdalifah, Musdalifah (Universitas Cokroaminoto Palopo, 2025)
Kampus Mengajar provides valuable opportunities for students to contribute directly as teaching partners at various levels of education, including elementary, junior high, and senior high schools, with a primary focus on improving learning quality and strengthening students’ literacy and numeracy skills, especially in schools that require additional support. The research investigates about a reflective teaching report which aimed to explore educational interventions and their impact. Employing qualitative descriptive approach using narrative reflection to document the author’s experience during the Kampus Mengajar Batch 7 Program at SD Negeri 61 Lekkong, Enrekang Regency, South Sulawesi. Data were collected primarily through daily reflective journaling throughout the program, feedback from the Field Supervisor and Mentor Teacher, and documentation of implemented activities, including reading corners, literacy and numeracy boards, the Market Day program, the English Club, and library revitalization. The findings reveal that literacy programs that fostered a reading culture, engaging numeracy activities that promoted real-life mathematical application, the integration of digital learning tools to enhance student participation, character education to instill essential values, and environmental awareness projects that encouraged responsibility toward nature. These results suggest that close collaboration with school stakeholders to ensure contextual relevance and long-term sustainability. By grounding approach in the actual conditions and culture of school, the programs succeeded in creating a positive impact not only on students’ academic performance but also on their personal development and enthusiasm for learning.